Disability and torture: exception, epistemology and 'black sites'. Issue 3 (4th May 2017) - Wadiwel, Dinesh
Abstract: Taking into consideration the November 2015 Australian Government Senate Standing Committees on Community Affairs final report on violence towards people with disability in institutional and residential settings, this paper explores the framing and epistemology of torture as practised against people with disability in sites of incarceration. Examining Giorgio Agamben's account of biopolitical sovereignty, this paper considers torture against people with disability as facilitated by legal exception. Extending this perspective further, and drawing on scholarship which examines anti-black violence in the context of policing and mass incarceration, it is argued that torture against people with disability constitutes an epistemic problem, where people with disability are framed as available for excessive violence without recourse to justice systems. This essay argues for more attention to the links between the torture experienced by people with disability in different sites of incarceration and systemic violence against racialized populations, particularly in the context of mass imprisonment.